(untitled) (CIPEEX, 2025)
Oral hormonal contraceptives are widely used as the primary method of preventing unwanted pregnancy and controlling premenstrual symptoms. Because it is a reversible and easily accessible method, available free of charge through the Unified Health System (SUS), it has become popular among women. However, it should be noted that indiscriminate use of these contraceptives can cause many side effects and adverse reactions ranging from mild symptoms, such as headache, fatigue, and nausea, to more serious effects, such as an increased risk of metabolic and cardiovascular disorders and the development of tumors. Thus, this study aims to investigate the main disorders associated with long-term use of oral hormonal contraceptives. This is a literature review conducted in the Google Scholar, Scielo, MEDLINE, and LILACS databases, focusing on the impacts of these contraceptives on women. The purpose is to promote reflection on the most common undesirable effects resulting from the use of oral hormonal contraceptives, presenting their formulation and examining how the subject is addressed at the beginning of the menstrual cycle and, consequently, throughout women’s adult lives and its ramifications. This would provide information for both women who use the medication and health professionals to assist in deciding which contraceptive method to adopt.